Raphalli et alcheriae, barracae sive patua. Términos de habitación humana en el latín medieval del reino de Valencia - Mesa Sanz, Juan Francisco (Influencias léxicas de otras lenguas en el latín medieval, 2011)
Synchronic study of the semantic class of habitacio in Liber privilegiorum civitatis et Regni Valencie and in Libre del Repartiment del Regne de Valencia. The obtained result is the location on this semantic class for the possible discriminating words of the so-called Valencian Latin. These words are in its majority arabisms.